Partial nephrectomy case report: Lower pole segmental vein thrombus - Brian Calio; Tara Morgan (Urology Video Journal)
Here we present a case of a partial nephrectomy of a mass with unanticipated but recognized segmental vein involvement. We were able to safely and completely remove the mass with its vein component and will describe in this video some visual cues and tips for both the surgeon and, importantly, the bedside assistant that can help aid in identification and removal of such tumors while minimizing the risk of leaving cancer behind. In this video we hope to convey the importance of a visual recognition of the tissue plane between the mass and the parenchyma, the need for a coordinated exposure between the surgeon and beside assistant to allow for optimal visualization of the tissue plane; as well as the anticipation for irregular tumor growth and the implementation of appropriate adjustments to minimize positive surgical margins.